Patient survival on haemodiafiltration and haemodialysis: a cohort study using the Australia and New Zealand Dialysis and Transplant Registry. Issue 2 (13th August 2018) - See, Emily J; Hedley, James; Agar, John W M; Hawley, Carmel M; Johnson, David W; Kelly, Patrick J; Lee, Vincent W; Mac, Kathy; Polkinghorne, Kevan R; Rabindranath, Kannaiyan S; Sud, Kamal; Webster, Angela C
Abstract: Background: It is unclear if haemodiafiltration improves patient survival compared with standard haemodialysis. Observational studies have tended to show benefit with haemodiafiltration, while meta-analyses have not provided definitive proof of superiority. Methods: Using data from the Australia and New Zealand Dialysis and Transplant Registry, this binational inception cohort study compared all adult patients who commenced haemodialysis in Australia and New Zealand between 2000 and 2014. The primary outcome was all-cause mortality. Cardiovascular mortality was the secondary outcome. Outcomes were measured from the first haemodialysis treatment and were examined using multivariable Cox regression analyses. Patients were censored at permanent discontinuation of haemodialysis or at 31 December 2014. Analyses were stratified by country. Results: The study included 26 961 patients (4110 haemodiafiltration, 22 851 standard haemodialysis; 22 774 Australia, 4187 New Zealand) with a median follow-up of 5.31 (interquartile range 2.87–8.36) years. Median age was 62 years, 61% were male, 71% were Caucasian. Compared with standard haemodialysis, haemodiafiltration was associated with a significantly lower risk of all-cause mortality [adjusted hazard ratio (HR) for Australia 0.79, 95% confidence interval (95% CI) 0.72–0.87; adjusted HR for New Zealand 0.88, 95% CI 0.78–1.00]. In Australian patients, there was also an association between haemodiafiltration and reduced cardiovascular mortality (adjusted HR 0.78, 95% CI 0.64–0.95). Conclusion: Haemodiafiltration was associated with superior survival across patient subgroups of age, sex and comorbidity.